THE USE OF MODERN TECHNOLOGİES İN TEACHİNG THE UZBEK LANGUAGE (American Journal of Research in Humanities and Social Sciences, 2023)
This article is about the use of modern technologies in the process of teaching the Uzbek language, thereby increasing the effectiveness of the lesson. It was also discussed about the active use of information media in classes to arouse interest in students.